CDCA7-associated global aberrant DNA hypomethylation translates to localized, tissue-specific transcriptional responses - Vukic, Maja; Chouaref, Jihed; Della Chiara, Veronica; Dogan, Serkan; Ratner, Fallon; Hogenboom, Jenna Z M; Epp, Trevor A; Chawengsaksophak, Kallayanee; Vonk, Kelly K D; Breukel, Cor; Ariyurek, Yavuz; San Leon Granado, David; et al. (Science advances, 2024)
Disruption of cell division cycle associated 7 (CDCA7) has been linked to aberrant DNA hypomethylation, but the impact of DNA methylation loss on transcription has not been investigated. Here, we show that CDCA7 is critical for maintaining global DNA methylation levels across multiple tissues in vivo. A pathogenic Cdca7 missense variant leads to the formation of large, aberrantly hypomethylated domains overlapping with the B genomic compartment but without affecting the deposition of H3K9 trimethylation (H3K9me3). CDCA7-associated aberrant DNA hypomethylation translated to localized, tissue-specific transcriptional dysregulation that affected large gene clusters. In the brain, we identify CDCA7 as a transcriptional repressor and epigenetic regulator of clustered protocadherin isoform choice. Increased protocadherin isoform expression frequency is accompanied by DNA methylation loss, gain of H3K4 trimethylation (H3K4me3), and increased binding of the transcriptional regulator CCCTC-binding factor (CTCF). Overall, our in vivo work identifies a key role for CDCA7 in safeguarding tissue-specific expression of gene clusters via the DNA methylation pathway.
Keywords: Animals; Nuclear Proteins; DNA; protein - isoformy; zvířata; Cell Cycle Proteins; Mice; Repressor Proteins; proteiny buněčného cyklu; jaderné proteiny; transkripční faktory; Transcription Factors; Protein Isoforms; represorové proteiny; DNA Methylation; metylace DNA; myši